Research trends and hotspots in climate adaptation of the agricultural system: A bibliometric analysis - Jiang, Bing; Deng, Xiaoshang; Chen, Hongbo; Cui, Lihang; Tang, Wenjie (Frontiers in Sustainable Food Systems, 2023)
Agricultural system is highly dependent on the natural environment, thus even a slight climate change can have a significant impact on it. Climate change has already caused a series of problems for the agricultural system, which makes improving climate adaptation of the agricultural system extremely important. In order to clarify the current research status, cooperation network, research hotspots and trends in climate adaptation of the agricultural system, we adopt the bibliometric method via CiteSpace to analyze the data collected from the Web of Science (WoS) Core Collection. Through the analysis of a number of publications, we found that the current research in climate adaptation of the agricultural system has entered a rapid development stage. Moreover, the United State of America (USA) is the most impactful country with the most publications in this field. In terms of institutions, the University of Leeds contributes most to the research in climate adaptation of the agricultural system. And its faculty, A. J. Dougill, is the author who contribute most to this field. By cluster analysis and burst analysis, we confirmed conceptual studies, ecologically venerable areas, and climate adaptation strategies are the hotspot in climate adaptation of the agricultural system, while impact assessment, governance and decision-making, farming system, and climate information service are the research trend in this field. This review is expected to help researchers quickly grasp the research situation in climate adaptation of the agricultural system and provide a reference for future research in this field.